Analysis for Science Librarians of the 2019 Nobel Prize in Chemistry: Lithium-Ion Batteries. Issue 1 (2nd January 2020) - Wrublewski, Donna T.
ABSTRACT: The 2019 Nobel Prize in Chemistry recognized three scientists who each contributed a key development to the lithium-ion battery. Ubiquitous in the portable devices of the modern world, overcoming the significant chemical challenges of working with lithium was no small feat. Stanley Whittingham demonstrated the first working rechargeable battery based on lithium ion transfer. John B. Goodenough designed a cathode that increased the battery voltage to commercially viable levels. Akira Yoshino designed a new anode without lithium metal that made the battery safe enough for mass production and use. The lithium-ion battery as we know it today would not exist without the discoveries from each of these researchers.